Awareness and knowledge of medical issues related to female athletes among track and field coaches - Tsukahara, Y.; Kamada, H.; Torii, S.; Yamamoto, H.; Yamasawa, F. (Open Access Journal of Sports Medicine, 2023)
Introduction: Little is known regarding medical knowledge pertaining to female athletes among track and field coaches and their interactions with female athletes regarding medical problems. Methods: Participants were track and field coaches (369 males and 43 females) with Japan Sport Association certification and they completed an anonymous survey on their knowledge of medical problems pertinent to female athletes including whether the coaches knew about the female athlete triad and relative energy deficiency in sports; their feelings about female athletes` use of contraceptive pills; whether they speak about menses with the female athletes; and whether they have a gynecologist for consultation regarding their medical problems. Results: Females coaches were significantly more likely to be aware of the triad (odds ratio (OR), 3.44; p = 0.003); to have access to a physician able to address the gynecological problems of female athletes (OR, 9.22; p < 0.001); and to talk to their female athletes about menses (OR, 2.30; p = 0.015) than their male counterparts. Coaches with more experience tended to be aware of the triad and relative energy deficiency in sports compared with those with = 5 years of experience. Conclusion: Females coaches are aware of the triad, talk about menses with their female athletes, and have access to a physician who can address gynecological problems with compared to male counterparts. Educating all coaches on these problems is essential to provide adequate support to female athletes.